Boosting cell performance and fuel utilization efficiency in a solar assisted methanol microfluidic fuel cell. (21st August 2020) - Kwok, Y.H.; Wang, Y.; Zhang, Y.; Zhang, H.; Li, F.; Pan, W.; Leung, D.Y.C.
Abstract: Solar generated hydrogen from an optimized P25 thin film of 3.2 mg/cm 2 with 0.25% of platinum as co-catalyst improves the peak power output of a methanol microfluidic fuel cell operated with a methanol to water ratio of 1:1 almost ninefold, from 22 mW/cm 2 to 213 mW/cm 2 . Different methanol to water ratios in the fuel tank generate similar amounts of hydrogen, but the cell performance has large variations due to the different oxidation kinetics of hydrogen and methanol in the fuel breathing anode, resulting in a mixed-potential anodic performance. The trade-off between power output and fuel utilization diminishes in this system. The methanol utilization efficiency at peak power operation increases from 50% (for 0.2 V) to 78% (for 0.5 V) for methanol to water ratio of 1:1. The result indicates that in-situ generation of hydrogen by solar light can be applied to both portable and large-scale stationary fuel cells. Graphical abstract: Image 1 Highlights: A compact solar fuel processor with Pt/P25 thin film was designed. Photo-reforming hydrogen from methanol solution to the microfluidic fuel cell. Peak power density was boosted by almost nine-fold under solar light illumination. Methanol utilization increased by 56%, achieving 78% at peak power output voltage.